Экспоненциальная дихотомия и ограниченные решения дифференциальных уравнений в пространстве Фреше - Бойчук, А.А.; Покутный, А.А. (Український математичний журнал, 2014)
Отримано необхідні та достатні умови існування обмежених розв'язків лінійних диференціальних рівнянь у простopi Фреше. Розв'язки побудовано з використанням сильного узагальнено-оберненого оператора. We establish necessary and sufficient conditions for the existence of bounded solutions of linear differential equations in the Fréchet space. The solutions are constructed with the use of a strong generalized inverse operator.